The sarcopenia and physical frailty in older people: multi-component treatment strategies (SPRINTT) project: description and feasibility of a nutrition intervention in community-dwelling older Europeans - Jyväkorpi, S K; Ramel, A; Strandberg, T E; Piotrowicz, K; Błaszczyk-Bębenek, E; Urtamo, A; Rempe, H M; Geirsdóttir, Ó; Vágnerová, T; Billot, M; Larreur, A; Savera, G; et al. (European geriatric medicine, 2021)
BACKGROUND: The "Sarcopenia and Physical Frailty in Older People: Multicomponent Treatment Strategies" (SPRINTT) project sponsored a multi-center randomized controlled trial (RCT) with the objective to determine the effect of physical activity and nutrition intervention for prevention of mobility disability in community-dwelling frail older Europeans. We describe here the design and feasibility of the SPRINTT nutrition intervention, including techniques used by nutrition interventionists to identify those at risk of malnutrition and to carry out the nutrition intervention. METHODS: SPRINTT RCT recruited older adults (≥ 70 years) from 11 European countries. Eligible participants (n = 1517) had functional limitations measured with Short Physical Performance Battery (SPPB score 3-9) and low muscle mass as determined by DXA scans, but were able to walk 400 m without assistance within 15 min. Participants were followed up for up to 3 years. The nutrition intervention was carried out mainly by individual nutrition counseling. Nutrition goals included achieving a daily protein intake of 1.0-1.2 g/kg body weight, energy intake of 25-30 kcal/kg of body weight/day, and serum vitamin D concentration ≥ 75 mmol/L. Survey on the method strategies and feasibility of the nutrition intervention was sent to all nutrition interventionists of the 16 SPRINTT study sites. RESULTS: Nutrition interventionists from all study sites responded to the survey. All responders found that the SPRINTT nutrition intervention was feasible for the target population, and it was well received by the majority. The identification of participants at nutritional risk was accomplished by combining information from interviews, questionnaires, clinical and laboratory data. Although the nutrition intervention was mainly carried out using individual nutritional counselling, other assisting methods were used as appropriate. CONCLUSION: The SPRINTT nutrition intervention was feasible and able to adapt flexibly to varying needs of this heterogeneous population. The procedures adopted to identify older adults at risk of malnutrition and to design the appropriate intervention may serve as a model to deliver nutrition intervention for community-dwelling older people with mobility limitations.
Keywords: Sarcopenia; Independent Living; lidé; křehkost; senioři; cvičení; studie proveditelnosti; Feasibility Studies; sarkopenie; Aged; Exercise; Frailty; samostatný způsob života; Humans